Testing the Effectiveness of “English Language” Course Book for Indonesian Senior High School Students - Rasyid, Risma; Tanasy, Novalia; Nasir, A. Muhajir (Elsya : Journal of English Language Studies, 2019)
English as an international language is one of the general subjects taught at school. Many school apply English as subject. From the explanation which has been explained above the researcher was research about course book. This study aims to know the effectiveness of the English course book by pre-experimental method with giving the students pre-test and post-test. The researcher conducted the first grade students in the senior high school in Maros specially at MA DDI Alliritengae Maros. The results show that learning outcomes after using the English Couse Book titled "English Language", it can be seen that the average value is 66.42 and the classical completeness is 15.79%. Where, the average learning outcomes are still less than 75 and the classical completeness is still less than 75%. So it can be said that the learning outcomes also do not meet the Minimum Completeness Criteria (KKM) specified. In conclusion, learning using the English Course Book titled "English Language" is not effective to be applied in class X.1 IPA MA. DDI Alliritengae Maros.